Toward Understanding the Quality of Subtitle Synchronization to Improve the Viewer Experience - Brito, Jessica O.; Santos, Celso A. S.; Guimarães, Rodrigo L.; , Thiago Felipe C. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2019: Proceedings of the 25th Brazilian Symposium on Multimedia and the Web, 2019)
Whoever has already downloaded a subtitle file from the Internet has probably had a bitter disappointment when finding that the subtitles were not synchronized in regards to the audiovisual content. This situation demonstrates that the quality of subtitle synchronization has the ability to impact, positively or negatively, the viewer experience. In this context, this work investigates the quality perception of subtitle synchronization from the perspective of subtitlers and users. Our observations are based on the analysis of data collected from 2 experiments involving a total of 32 participants and of data extracted from subtitle files. Our results suggest that the quality of subtitle synchronization is perceived differently among subjects of these 2 groups and that, in some cases, more “relaxed” synchronization directives do not impact negatively the viewer experience.